An Analysis Of Students’ Speaking Anxiety On Speaking Ability In Class X At MAN 2 Bengkulu City Based On Emha Abdurrahman’s Theory - Novan Hardiansah; Adisel; Dedi Efrizal (EDUCATION JOURNAL OF INDONESIA, 2024)
The objectives of this study were: 1) To find out the factors that influence student anxiety in public speaking 2) To find out some of the suggestions and efforts to deal with students' speech anxiety based on Emha Abdurrahman's theory, especially in class X MAN 2 Bengkulu City for the 2023-2024 Academic Year. The type of research used is field research, and is included in qualitative research. The informants in the study amounted to 21 people, namely class X students and English teachers. Data collection techniques in this study used observation, interviews, questionnaires and documentation. Based on the results of the analysis that has been done, it can be concluded that: 1)Students revealed some factors that cause them experiencing anxiety: The first interviewee stated that anxiety occurs because of low speaking skills, fear of making mistakes, and fear of being criticized, which causes low self-esteem. The second interviewee said that the anxiety happens because of the fear of misinterpretation, lack of vocabulary, lack of practice, the inability to control emotions, and feelings of inferiority. The interviewee also stated that when the interviewee saw someone who has a higher ability, a feeling of self-indulgence arose and caused excessive panic and nervousness. The third interviewee mentioned that anxiety occurs because of feelings of inferiority, fear of being wrong, fear of being laughed at, and being scolded by the lecturer. The fourth interviewee conveyed that anxiety happens because of the fear of making mistakes when speaking, lack of confidence, and the fear of getting a bad impression from the audience. 2) According to Emha Abdurrahman, speaking is a verbal explanation about a thing (problem) by stating the information clearly in front of the masses or the crowd at a certain time. The main key for someone to be able to successfully display speaking is due to the will of the person concerned. With there is a strong self-will to be able to give a good speech, then the concerned will certainly try to understand, understand, explore the ins and outs of problems before finally appearing in actual practice. With an attitude like this that can make a person like a lion podium if you appear carrying your belly and get success like that expected . For speech strategies, there are several that are often used: 1) Impromptu Strategy; 2) Memorization Strategy; 3) Manuscript Strategy; 4) Extemporary Strategy. Keyword : Speaking Ability, Anxiety, Emha Abdurrahman’s